2019
DOI: 10.1159/000502135
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival Outcomes of Metabolically Supported Chemotherapy with Gemcitabine-Based or FOLFIRINOX Regimen Combined with Ketogenic Diet, Hyperthermia, and Hyperbaric Oxygen Therapy in Metastatic Pancreatic Cancer

Abstract: Background: Despite introduction of new chemotherapeutic agents, outcomes of patients with metastatic pancreatic cancer are still poor. Metabolically supported chemotherapy (MSCT) is a novel approach targeting dysregulated energy mechanism of the tumor cell. Objectives: This study aimed to examine the efficacy of metabolically supported administration of chemotherapy combined with ketogenic diet, hyperthermia, and hyperbaric oxygen therapy (HBOT) in patients with metastatic pancreatic cancer. Method: This retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…In stage IV non-small cell lung cancer patients a KD combined with hyperthermia, hyperbaric oxygen, and short-term fasting prior to chemotherapy resulted in a 3 − 8 times longer overall and progression-free survival than expected from other studies applying the same type of chemotherapy [24]. In metastasized pancreatic cancer patients, the same combination of complementary treatments together with gemcitabine or FOLFIRINOX chemotherapy resulted in a median overall and progression-free survival of 15.8 months (95% CI, 10.5-21.1) and 12.9 months (95% CI, 11.2-14.6), respectively [25]. Finally, a randomized controlled trial in breast cancer patients receiving neoadjuvant chemotherapy found that a KD resulted in significantly longer overall survival compared to a control diet over a follow-up period of 30 months [22].…”
Section: Current State Of the Researchmentioning
confidence: 77%
“…In stage IV non-small cell lung cancer patients a KD combined with hyperthermia, hyperbaric oxygen, and short-term fasting prior to chemotherapy resulted in a 3 − 8 times longer overall and progression-free survival than expected from other studies applying the same type of chemotherapy [24]. In metastasized pancreatic cancer patients, the same combination of complementary treatments together with gemcitabine or FOLFIRINOX chemotherapy resulted in a median overall and progression-free survival of 15.8 months (95% CI, 10.5-21.1) and 12.9 months (95% CI, 11.2-14.6), respectively [25]. Finally, a randomized controlled trial in breast cancer patients receiving neoadjuvant chemotherapy found that a KD resulted in significantly longer overall survival compared to a control diet over a follow-up period of 30 months [22].…”
Section: Current State Of the Researchmentioning
confidence: 77%
“…Clinical evidence on the potential benefit of MSCT comes from clinical studies with pancreatic cancer patients and non-small cell lung cancer patients as well as from two case reports. In a recent study with stage IV ductal pancreatic adenocarcinoma patients, metabolically supported administration of chemotherapy resulted in promising survival outcomes with a reported median survival of 15.8 months [9]. Another recent study reported encouraging results in stage IV non-small cell lung cancer with a mean 42.9 months overall survival rate [10].…”
Section: Discussionmentioning
confidence: 99%
“…All eligible patients were advised to adapt a ketogenic diet during the study period and they were asked to fast for 12 hours before each chemotherapy session. In addition to the premedication with 45.5 mg pheniramine maleate and 0.25 mg palonosetron HCl, each patient received regular insulin (Humulin® R) in doses ranging between 5-20 IU prior to chemotherapy administration in order to achieve a state of mild hypoglycemia with blood glucose levels around 50-60 mg/dl for normoglycemic patients and in accordance with MSCT protocols [7][8][9][10]. Following each MSCT administration, patients received a 60-minute session of hyperthermia and a 60-minute session of HBOT.…”
Section: Administration Of Metabolically Supported Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations